Intravenously usable fully serotype 3 oncolytic adenovirus coding for CD40L as an enabler of dendritic cell therapy - Sadia Zafar (OncoImmunology, 2017)
Vaccination with dendritic cells (DCs), the most potent professional antigen-presenting cells in the body, is a promising approach in cancer immunotherapy. However, tumors induce immunosuppression in their microenvironment that suppresses and impairs the function of DCs. Therefore, human clinical trials with DC therapy have often been disappointing. To improve the therapeutic efficacy and to overcome the major obstacles of DC therapy, we generated a novel adenovirus, Ad3-hTERT-CMV-hCD40L, which is fully serotype 3 and expresses hCD40L for induction of antitumor immune response. The specific aim is to enhance DCs function. Data from a human cancer patient indicated that this capsid allows effective transduction of distant tumors through the intravenous route. Moreover, patient data suggested that virally produced hCD40L can activate DCs in situ. The virus was efficient in vitro and had potent antitumor activity in vivo. In a syngeneic model, tumors treated with Ad5/3-CMV-mCD40L virus plus DCs elicited greater antitumor effect as compared with either treatment alone. Moreover, virally coded CD40L induced activation of DCs, which in turn, lead to the induction of a Th1 immune response and increased tumor-specific T cells. In conclusion, Ad3-hTERT-CMV-hCD40L is promising for translation into human trials. In particular, this virus could enable successful dendritic cell therapy in cancer patients.